Balance and Fall Risk Assessment in Community-Dwelling Older Adults after Recovery from COVID-19: A Cross-Sectional Study - Amira E. El-Bagalaty; Mariam El-Sayed Mohamed; Osama R. Abdelraouf; Mohamed A. Abdel Ghafar; Alshaimaa K. Abdelaal; Abdelgalil A. Abdelgalil; Gihan S. Mousa (MDPI AG, 2023)
Background: SARS-CoV-2 atypical symptoms in older persons include falls, confusion, dizziness, and unusual weariness. Falls and their consequences are among the most prevalent causes of disability among older adults, significantly lowering quality of life and resulting in the loss of independence as well as impaired psychosocial functioning. The study purpose was to examine the impact of the SARS-CoV-2 infectious disease on balance in community-dwelling older adults. Methods: Sixty-four older adults aged ≥ 60 years from both sexes, 31 treated for SARS-CoV-2 infection and 33 matched normal controls participated in the study. The Biodex Stability System (BSS) and Berg Balance Scale (BBS) were used for evaluation of balance and fall risk. The correlation between the Biodex overall stability index and the Berg Balance Scale score was investigated. Results: When compared to controls, the SARS-CoV-2 group had significantly higher values of the Biodex overall stability index (OSI) (p = 0.011), anterior-posterior stability index (APSI) (p = 0.013), mediolateral stability index (MLSI) (p = 0.018), and fall risk index (FRI) (p = 0.008), as well as statistically lower scores on the Berg balance scale (p = 0.003). A moderate negative correlation was found between the two assessment tools in the SARS-CoV-2 group. Conclusion: Balance impairment and an increased risk of falling are among the outcomes of SARS-CoV-2 in community-dwelling older adults.